Implementation of Duties and Functions of the Minahasa Regency Regional Inspectorate - Runtunuwu, Martha N. F.; Mokat, Jetty Erna Hilda; Pangkey, Itje (Technium Social Sciences Journal, 2021)
The aims of this research are to; 1) describe and analyze the implementation of the Inspectorate's duties and functions in the implementation of internal control over performance and finances through audits, reviews, evaluations, monitoring/monitoring and other supervisory activities; 2) analyze and explain the determinant factors that determine the implementation of the functions and functions of the Inspectorate in the implementation of internal control over performance and finance through audits, reviews, evaluations, monitoring/monitoring and other supervisory activities. This study uses a qualitative research approach with qualitative descriptive methods. The findings found in this study are: The implementation of the Inspectorate function of Minahasa Regency in terms of the implementation of the supervisory function has not been optimal even though regulations related to policies have been made. This research takes place at the Regional Inspectorate of Minahasa Regency, the target is the Functional Officer of the Supervisory Administration of Government Affairs in the region (PPUPD).